Do C-H...O hydrogen bonds contribute to the stability of nucleic acid base pairs? - Leonard, G; McAuley-Hecht, K; Brown, T; Hunter, W (1995)
The possible formation of inter-base C-H.O hydrogen bonds in A.T, A.U and certain non-Watson-Crick base pairs is examined. A geometrical analysis in conjunction with implications for the thermodynamic stability of the base pairs suggests that C-H.O hydrogen bonds could form in nucleic acid base pairs. They may alleviate destabilizing interactions that would arise if an unsatisfied hydrogen-bond acceptor were present and mediate secondary hydrogen-bonding effects in these base pairs.